Stock market response to the Russia-Ukraine war: Evidence from an emerging market - KELEŞ, EMRAH (My University, 2023)
This study examines the role of financial factors contributing to firms’ resilience during the Russia-Ukraine war. Event study results show a significant adverse reaction, which started before the official war announcement and grew over time. Further, cross-sectional analyses uncover that the negative effect is mitigated for larger and more profitable firms but amplified for high market-cap firms with high cash and debt-holding; both effects are more pronounced for non-financial companies. This study contributes by exploring Turkey as a unique emerging market setting due to its significant geopolitical position, strategic trade, and business partnership with the European Union and Russia.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Sosyoloji; İşletme; Social Sciences and Humanities; Geography; Sociology; Management; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Yerbilimleri; Ekonomi ve İş; Sosyal Bilimler Genel; COĞRAFYA; İŞLETME; PLANLAMA VE GELİŞİM; Natural Sciences (SCI); Social Sciences (SOC); GEOSCIENCES; ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; GEOGRAPHY; BUSINESS; PLANNING & DEVELOPMENT; İşletme ve Uluslararası Yönetim; Sosyal Bilimler ve Beşeri Bilimler; Coğrafya, Planlama ve Geliştirme; Gelişim; Business and International Management; Social Sciences & Humanities; Geography, Planning and Development; Development; Emerging market; resilience; Russia-Ukraine war; stock returns; Emerging market; resilience; Russia-Ukraine war; stock returns